Sustainable floodplains: linking e-flows to floodplain management, ecosystems, and livelihoods in the Sahel of North Africa - O'Brien, G.C.; Dickens, Chris; Baker, C.; Stassen, R.; Weert, F. van (MDPI, 2020)
Floodplains are particularly important in the semi-arid region of the Sub-Sahelian Africa. In this region, water governance is still being developed, often without adequate information and technical capacity for good, sustainable water resource management. However, water resources are being allocated for use with minimal sustainability considerations. Environmental flows (e-flows) include the quantity and timing of flows or water levels needed to meet the sustainable requirements of freshwater and estuarine ecosystems. Holistic regional scale e-flows linked to floodplain management can make a noticeable contribution to sustainable floodplain management. The Inner Niger Delta (IND) in Mali is an example of a vulnerable, socio-ecologically important floodplain in the Sahel region of North Africa that is being developed with little understanding of sustainability requirements. Although integrally linked to the Upper Niger River catchment, the IND sustains a million and half people within the region and exports food to surrounding areas. The flooding of the Delta is the engine of the socio-economic development as well as its ecological integrity. This paper aims to demonstrate the contribution that holistic regional e-flow assessment using the PROBFLO approach has to achieving floodplain sustainability. This can be achieved through the determining the e-flow requirements to maintain critical requirements of the ecosystems and associated services used by local vulnerable human communities for subsistence and describing the socio-ecological consequences of altered flows. These outcomes can contribute to the management of the IND. In this study, the socio-ecological consequences of altered flows have been evaluated by assessing the risk of alterations in the volume, duration, and timing of flows, to a number of ecological and social endpoints. Based on the risk posed to these endpoints by each scenario of change, an e-flow of 58% (26,685 million cubic meters (MCM) of water annually) was determined that would protect the ecosystem and maintain indicator components at a sustainable level. These e-flows also provide sustainable services to local communities including products for subsistence and limit any abnormal increases in diseases to the vulnerable African communities who live in the basin. Relative risk outputs for the development scenarios result in low-to-high-risk probabilities for most endpoints. The future development scenarios include insufficient flows to maintain sustainability during dry or low-flow periods with an increase in zero flow possibilities. Although unsuitable during the low-flow or dry periods, sufficient water is available through storage in the basin to meet the e-flows if these scenarios were considered for implementation. The IND is more vulnerable to changes in flows compared to the rivers upstream of the IND. The e-flow outcomes and consequences of altered flow scenarios has contributed to the management of vulnerable IND floodplains and the requirements and trade-off considerations to achieve sustainability.